The Formative Potential of Interactive Instructional Strategies in Oral Assesment for Romanian as a Foreign Language (Levels A1-A2) - Putină, Dorina; Corobcean, Doina (Didactica Danubiensis, 2026)
The article aims to highlight the role and formative potential of interactive teaching strategies in the oral assessment of communicative competence in Romanian as a foreign language at the A1–A2 levels, emphasizing their importance in supporting progressive, intentional learning anchored in authentic communicative situations. The approach is grounded in the updated orientations of the Common European Framework of Reference for Languages and in recent research on formative assessment and foreign language pedagogy, which advocate moving beyond traditional approaches focused exclusively on isolated linguistic skills. The analysis is conducted from a theoretical–applied perspective, drawing on the integrative model of language activities — reception, production, interaction, and mediation — and examining how interactive teaching strategies can be employed in formative oral assessment. The findings indicate that oral assessment, conceived as a formative process, fosters meaning-making, negotiation of meaning, and the development of communicative competence in authentic contexts. The study provides useful reference points for teachers and teacher trainers involved in teaching Romanian as a foreign language, contributing to the optimization of formative oral assessment practices. The originality of the article lies in the coherent integration of interactive teaching strategies into formative oral assessment, highlighting their potential to stimulate learners’ active engagement, self-regulated learning, and the socio-pragmatic dimension of communication.